Native tissue repair versus mesh repair in pelvic organ prolapse surgery - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2017)
In pelvic organ prolapse, the anatomical defects develop at the anterior (anterior vaginal wall), the posterior (posterior vaginal wall) and the apical (the uterus/cervix or the apex of the vagina, vaginal vault or cuff scar after hysterectomy) compartments. These defects occur in more than one compartment. Treatment of pelvic organ prolapse is commonly surgical, aiming to restore the anatomy of structures supporting the pelvic organs. The surgical repair techniques are classified as native tissue repair (NTR)' when only pelvic organ support tissues are used and augmented repair (AR)' when some other material (prosthesis or graft) is used to reinforce the defective support system. In this review, issues related to the basic science of meshes, and NTR versus mesh or graft AR procedures for pelvic organ prolapse are discussed while considering the varying risks and benefits according to the prolapsed compartment.
Keywords: Native tissue repair; mesh repair; pelvic organ prolapse surgery; VAGINAL WALL PROLAPSE; STRESS URINARY-INCONTINENCE; PROSPECTIVE RANDOMIZED-TRIAL; COATED TRANSVAGINAL MESH; ANTERIOR COLPORRHAPHY; RISK-FACTORS; POLYPROPYLENE MESH; FASCIA LATA; RECTOCELE REPAIR; RECONSTRUCTIVE SURGERY